Il Servizio Sanitario Nazionale alla prova dell’emergenza CoViD-19: il rischio di una sanità diseguale (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The Italian National Health Service, characterized by the principles of universality, equality and fairness, has undergone changes over the years that have involved these essential characteristics. The decrease in financial resources was the first element that touched the Italian health organization. The spread of CoViD-19 has attacked the balance of healthcare in Italy and put the equality of the entire care system at risk.
Keywords: CoViD-19; pandemic emergency; unequal health; health policy; public spending